2021
DOI: 10.1007/s00146-021-01253-6
|View full text |Cite
|
Sign up to set email alerts
|

AI as a boss? A national US survey of predispositions governing comfort with expanded AI roles in society

Abstract: People's comfort with and acceptability of artificial intelligence (AI) instantiations is a topic that has received little systematic study. This is surprising given the topic's relevance to the design, deployment and even regulation of AI systems. To help fill in our knowledge base, we conducted mixed-methods analysis based on a survey of a representative sample of the US population (N = 2254). Results show that there are two distinct social dimensions to comfort with AI: as a peer and as a superior. For both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 50 publications
(61 reference statements)
1
10
0
Order By: Relevance
“…Moreover, previous studies in the domain of technology adoption have shown that persons of advanced age may have a higher propensity for resistance towards change. Certain senior educators may have lacked the chance to use technology into their pedagogical approaches throughout their professional trajectories, Mays et al (2021). Ethical issues include privacy of data and stereotype.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous studies in the domain of technology adoption have shown that persons of advanced age may have a higher propensity for resistance towards change. Certain senior educators may have lacked the chance to use technology into their pedagogical approaches throughout their professional trajectories, Mays et al (2021). Ethical issues include privacy of data and stereotype.…”
Section: Discussionmentioning
confidence: 99%
“…This is problematic with tools like ChatGPT, where the information provided will probably be judged based on the user's beliefs about the perceived sources, for instance. However, systematic surveys about people's beliefs, experience, or knowledge concerning specific AI fields are rare, with the majority dealing with perceptions of AI in general or in the medical context [40][41][42][43] and surveys even leaving out the specific field of ATG entirely [44]. To the best of our knowledge, there is no current investigation specifically on people's beliefs about ATG or their concepts about its function, responsibilities, or data sources.…”
Section: The Current Researchmentioning
confidence: 99%
“…Researchers employing the term "AI" in the sense of "artificial narrow intelligence" may be justified in discussing the countless ways in which "AI" has for years been playing significant roles in managing human workers, either for good or ill (see, e.g., De Stefano 2020a, De Stefano 2020b, Dong et al 2022), while researchers who employ the term "AI" to refer to something more akin to "artificial general intelligence" may be equally justified in considering how many years it will be before "AI" is introduced into workplaces to begin managing human workers and in investigating the implications that may arise when that occurs (see, e.g., Chamorro-Premuzic and Ahmetoglu 2016, Mélypataki 2019, Mays et al 2021.…”
Section: Considerations In Analyzing the Capacities And Limitations O...mentioning
confidence: 99%
“…This text seeks to analyze potential organizational roles of the "AI boss" understood as a particular sort of entity which -while not an "entity" in the same sense as a human beingis nevertheless more than simply a "process" or a particular technologically savvy "approach" to organizational management. The fact that an AI boss will be popularly perceived by human workers as an entity (see, e.g., Chamorro-Premuzic and Ahmetoglu 2016, Captain 2017, Kruse 2019, Mélypataki 2019, Mays et al 2021 is not simply an effect of human cognitive biases but a reflection of the AI boss's nature, which differentiates it from workplace processes like digitization, digitalization, and algorithmization whichwhile emerging during roughly the same time periodare conceptually distinct from AI.…”
Section: The Ai Boss As An "Entity" Rather Than An "Approach" or "Pro...mentioning
confidence: 99%